Effect of Multi-Variable Mix Composition on the Setting Time and Flow Properties of Fly Ash-GGBFS Geopolymer Mortar - Bayu Rahmat Ramadhan; Andi Arham Adam; Sri Nur Akifa; Suci Amalia Namira Wahidin; Novacharisma Vindiantri Verucha; Misel Borro Allo (Borneo Engineering: Jurnal Teknik Sipil, 2025)
The development of eco-friendly construction materials increasingly emphasizes the utilization of industrial waste, with fly ash being a prominent alternative binder to Portland cement. However, Type F fly ash exhibits limitations due to its inherently low calcium (CaO) content, which results in slow geopolymerization reactivity and typically necessitates high-temperature curing to achieve optimal early strength. This research aims to optimize the utilization of 100% fly ash as a binder in geopolymer mortar by incorporating Ground Granulated Blast Furnace Slag (GGBFS). GGBFS serves as a source of reactive calcium, specifically to accelerate C-A-S-H gel formation. The alkaline activator used comprises NaOH and Na₂SiO₃ solutions, varied at specific ratios. The experimental program investigates the influence of three key parameters: GGBFS content (10%, 20%, and 30% by fly ash weight), activator/binder ratio (30%, 35%, and 40%), and aggregate/binder ratio (2.25, 2.5, and 2.75). The primary focus is to evaluate their effect on the fresh properties of geopolymer mortar, particularly flowability and setting time, under ambient curing conditions (without heat treatment). The findings of this study are expected to demonstrate that GGBFS addition significantly enhances early reactivity and facilitates the development of geopolymer mortar suitable for ambient temperature applications. This research is anticipated to contribute to the advancement of sustainable construction materials through the optimal utilization of industrial waste, especially for applications where high-temperature curing is impractical.